Penyuluhan Tanda dan Gejala Campak pada Anak di Lingkungan Sekolah Dasa - Siti Rouchmana; Veny Nur Ramatia; Kania Adistyawati Marijadi; Rini Eka Pakerti (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2026)
Measles is an infectious disease caused by viruses of the genus Morbillivirus and can attack the respiratory tract, immune system, as well as the skin. Measles cases in Indonesia are still relatively high, which is characterized by a high incidence rate and the discovery of extraordinary events (KLB) so that knowledge of measles disease is needed in the community. The purpose of this activity is to increase the knowledge of students in class V-A SDN 016 Sungai Pinang Samarinda about the signs and symptoms of measles in children in the elementary school environment. Health promotion activities use powerpoint media, leaflets, and educational videos. The activity began with a pre-test, material delivery, mini quiz, and post-test. This activity was attended by 28 participants. The results of health promotion activities in class V-A SDN 016 Sungai Pinang Samarinda were 80.32% pre-test average and 95% post-test average and Wilcoxon Signed Ranks Test results showed a significance value of p